PIGMENT COMPOUNDS OF THE VEGETATIVE ORGANS OF АMARANTH(AMARANTHUSSPP.)AS A SOURCE OF NATURAL ANTIOXIDANTS - Tynykulov , M.K.; Kornilova , A.A.; Kuznecova , M.A.; Sadykov , A.M.; Yessenzholov , B.Kh.; Utaubayeva , A.U.; Suleimen , A. (Eurasian Journal of Applied Biotechnology, 2025)
In this study, a comprehensive assessment of 23 amaranth genotypes was carried out in order to identify forms with high productivity and high content of antioxidant pigments (chlorophylls, betalains, and carotenoids) adapted to the conditions of the arid agro-climatic zone of Northern Kazakhstan. As part of the work, the following tasks were solved: agromorphological and biochemical characterization of genotypes, determination of the content of antioxidant pigments in vegetative organs, assessment of green mass yield, calculation of heritability coefficients and genetic variation of traits, correlation analysis, as well as identification of promising genotypes and donors for subsequent breeding. The results showed high genetic variability in all the studied traits, confirmed by significant heritability coefficients and stability of indicators. Correlation analysis revealed a positive relationship between antioxidant pigments and a weak negative relationship with the yield of green mass. Promising genotypes (VA27, VA26, VA24, VA42, VA38) with an optimal combination of traits were identified, as well as donor genotypes VA25 and VA43 for breeding work. The practical significance of the study lies in the possibility of using the data obtained in the development of new varieties of amaranth with a high content of biologically active substances resistant to drought, for functional nutrition, pharmaceuticals and the agro-industrial sector.